2007
DOI: 10.1002/hep.21672
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation associated with hepatitis C virus infection perturbs hepatic transforming growth factor β signaling, promoting cirrhosis and hepatocellular carcinoma

Abstract: Many patients with chronic hepatitis caused by hepatitis C virus (HCV) infection develop liver fibrosis with high risk for hepatocellular carcinoma (HCC), but the mechanism underling this process is unclear. Conversely, transforming growth factor beta (TGF-␤) activates not only TGF-␤ type I receptor (T␤RI) but also c-Jun N-terminal kinase (JNK), which convert the mediator Smad3 into two distinctive phosphoisoforms: C-terminally phosphorylated Smad3 (pSmad3C) and linker-phosphorylated Smad3 (pSmad3L). Whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
264
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(294 citation statements)
references
References 28 publications
24
264
1
5
Order By: Relevance
“…We had reported previously that there were independent and additive interaction among the tumor necrosis factor 308.2 allele, substance use habits, and chronic HBV/HCV infection on risk for HCC (Jeng et al, 2009). In fact, areca nut may mediate proinflammatory and fibrogenic cytokines such as tumor necrosis factor α and transforming growth factor (TGF) β and reduce antifibrotic cytokine (interferon-γ) (Jeng et al, 2007;Matsuzaki et al, 2007;Angadi and Rao, 2011). Additionally, TGF β favors collagen production and decreases the degradation of collagen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had reported previously that there were independent and additive interaction among the tumor necrosis factor 308.2 allele, substance use habits, and chronic HBV/HCV infection on risk for HCC (Jeng et al, 2009). In fact, areca nut may mediate proinflammatory and fibrogenic cytokines such as tumor necrosis factor α and transforming growth factor (TGF) β and reduce antifibrotic cytokine (interferon-γ) (Jeng et al, 2007;Matsuzaki et al, 2007;Angadi and Rao, 2011). Additionally, TGF β favors collagen production and decreases the degradation of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TGF β favors collagen production and decreases the degradation of collagen. Moreover, chronic inflammation associated with HBV/HCV infection shifts hepatic TGF β signaling from tumor-suppression to fibrogenesis, accelerating liver fibrosis and increasing risk for HCC (Matsuzaki et al, 2007;Murata et al, 2009). This information may interpret the interaction between habitual BQ chewing and chronic HBV/HCV infection on risk of HCC (Tsai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic liver inflammation has been associated with a shift in signaling from tumor growth factor beta resulting in a change from tumor suppression to fibrosis and carcinogenesis (51). Proliferative changes in hepatic tissue related to ongoing inflammation from hepatitis are associated with repeated cycles of cell death and regeneration (50).…”
Section: Carcinogenic Properties Of Hcvmentioning
confidence: 99%
“…There are also several CAGA boxes in the PAI-1 promoter to which the TGF-β-activated nuclear Smad3/Smad4 heterodimer binds (Dennler, Itoh et al 1998). Meanwhile, other signaling pathways activated by TGF-β, include Erk in the MAPK pathway (Harradine and Akhurst 2006), Jnk (Matsuzaki, Murata et al 2007), P38 kinase (Vayalil, Iles et al 2007) and PI3…”
Section: Pai-1 Regulation By Tgf-βmentioning
confidence: 99%
“…In renal mesangial cells, TGF-β-induced PI3 Kinase/Akt signaling enhances Smad-mediated PAI-1 expression by promoting CBP-mediated Smad3 acetylation (Das, Ghosh-Choudhury et al 2008). Matsuzaki reported that Jnk, activated by TGF-β, phosphorylates Smad3 at the linker region (pSmad3L), which increases PAI-1 expression in heptocellular carcinoma (HCC) (Matsuzaki, Murata et al 2007). …”
Section: Pai-1 Regulation By Tgf-βmentioning
confidence: 99%